Trollhunters - Toro, Guillermo del, 1964-; Kraus, Daniel, 1975- (Hyperion, an imprint of Disney Book Group, 2015)
Everything changes for San Bernardino teenage suburbanite Jim Sturges when a 45-year old mystery resurfaces, threatening the lives of everyone in his seemingly sleepy town. Soon Jim has to team up with a band of unlikely (and some un-human) heroes to battle the monsters he never knew existed.